2016
DOI: 10.3389/fvets.2015.00080
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic–Pharmacodynamic Modeling of Enrofloxacin Against Escherichia coli in Broilers

Abstract: The purpose of the present study was to establish a pharmacokinetic/pharmacodynamic (PK/PD) modeling approach for the dosage schedule design and decreasing the emergence of drug-resistant bacteria. The minimal inhibitory concentration (MIC) of 929 Escherichia coli isolates from broilers to enrofloxacin and ciprofloxacin was determined following CLSI guidance. The MIC50 was calculated as the populational PD parameter for enrofloxacin against E. coli in broilers. The 101 E. coli strains with MIC closest to the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
34
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 48 publications
7
34
1
Order By: Relevance
“…The PK and residue of ENR in the serum of goats, pigs, calves, horses, sheep, and broilers have already been investigated in previous reports (Kaartinen et al, 1995; Giguère et al, 1996; Mckellar et al, 1997, 1999; Anadón et al, 1999; Elmas et al, 2001; Sang et al, 2015; Haag et al, 2016). However, most ENR products were difficult to feed in forage or water because of poor palatability.…”
Section: Discussionmentioning
confidence: 97%
“…The PK and residue of ENR in the serum of goats, pigs, calves, horses, sheep, and broilers have already been investigated in previous reports (Kaartinen et al, 1995; Giguère et al, 1996; Mckellar et al, 1997, 1999; Anadón et al, 1999; Elmas et al, 2001; Sang et al, 2015; Haag et al, 2016). However, most ENR products were difficult to feed in forage or water because of poor palatability.…”
Section: Discussionmentioning
confidence: 97%
“…These MDR organisms carry antibiotic-resistant genes with the potential to spread to other populations 28 . The abundant use of antibiotics in poultry farms has been associated with treatment failure and the development of antibiotic resistance itself 29 . A study showed that E. coli from poultry in China were resistant to at least 18 different antibiotics 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Clinical pathogenic E. coli isolates (n = 929) were previously collected from cases of broilers colibacillosis and initially screened for resistant to ciprofloxacin 29 . Of the 929 isolates, 45 strains with high MICs ( ≥ 16 µg/mL) against ciprofloxacin were selected for this study, due to the fact that chicken is the source of ciprofloxacin-resistant human E. coli 96 98 .…”
Section: Methodsmentioning
confidence: 99%
“…The PK features of TIL have already been studied in many species, including broiler chickens [ 23 ], equine [ 4 ], swine [ 25 ], goats [ 22 ], and rats [ 18 ]; however, PK investigations of TIL in infected animals are quite few. The PK profiles of a drug can be influenced by the pathophysiological changes during an infection, and PK parameters in infected animals are more close to the clinical conditions [ 15 24 ]. As previously reported, physiological and biochemical differences such as body temperature, plasma protein binding ratio, blood pressure, anemia, and liver function in healthy and diseased animals can result in changes to a drug's PK profile and parameters [ 28 ].…”
Section: Introductionmentioning
confidence: 99%